Introducing “ Undha Usuk” Javanese Language Through Children Drama Performance in Festival Kampoeng Pejoeang at Trate, Ngadiluwih - Encil Puspitoningrum; Marista Dwi Rahmayantis (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
Undha usuk in the Javanese language increasingly forgotten by the children in the Trate village, Ngadiluwih sub-district. The progress of the times, as well as the rise of technology,  makes children seems forgotten in their own regional language politeness. Innovative and educational activities are needed to overcome this. One of them is by staging child drama. Staging children's drama is an activity that integrates various language skills such as reading, listening, and speaking. The staging of children drama in Trate village, Ngadiluwih sub-district can be held in Kampoeng Pejoeang festival to celebrate independence day. The purpose of this article is to describe the technique of child drama performances in the festival Kampoeng Pejoeang as a strategy to introduce undha usuk in the Javanese language to children at Trate village, Ngadiluwih sub-district. The data obtained comes from observations and interviews. Drama learning theory, as well as language skills, especially undha ushuk Javanese language,  are combined in this article so that this strategy can be adapted elsewhere.